Monitoring the Reproductive Status of Sambar Deer (Cervus unicolor Kerr) Based on Sexual Behavior in Livestock Area of Palangka Raya City - Ma'rifah, Siti; Pudjirahaju, Asri; Sujoko, Heri; Rafli, Ferdian (Fakultas Peternakan, Universitas Padjadjaran, 2024)
AbstractThe existence of Sambar Deer (Cervus unicolor Kerr) is increasingly threatened due to habitat destruction and illegal hunting. However, with proper habitat management, this decline can be prevented. One of the Sambar deer-protected areas in Central Kalimantan is the Livestock Area of Palangka Raya City. This research aims to monitor the reproductive status of sambar deer based on sexual behavior in the Livestock Area of Palangka Raya City, Central Kalimantan. This research used six samples of sambar deer consisting of two female deer with sample codes A1&A2, two female deer with sample codes B1&B2 and two male deer with sample codes J1&J2. This research used three methods, namely Focal Animal Sampling, Ad Libitum Sampling, and One Zero Sampling. The results show that sexual activity is the lowest activity with a percentage of 1.9% (average time 13 minutes) per 11 hours. Meanwhile, the ANOVA test results show no significant difference in sexual activity between the deer groups. Keywords: Sexual Activity, Sambar Deer